Pengaruh Promosi dan Diskon terhadap Perilaku Belanja Impulsif Wanita di Toko Gaudi Makassar - Rifa'atul Mahmudah; Rahmat Ferdiansyah; Fitriana Fitriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine the effect of promotions and discounts on women's impulse shopping behavior at Gaudi Makassar store. As well as analyzing which variable has a more dominant significant effect on women's impulsive shopping behavior at Gaudi Makassar stores. This research was conducted in Makassar city with a sample size of 50 respondents who visited Gaudi store. The data analysis used is descriptive to explain the research data. Meanwhile, to analyze quantitative data using multiple linear regression analysis using spss version 27. The results showed that partially the promotion variable had no significant effect on the impulsive shopping behavior of women at the Gaudi Makassar store. The discount variable partially has a significant and positive effect on the impulsive shopping behavior of women at the Gaudi Makassar store. While simultaneously the promotion variable and the discount variable affect the impulsive shopping behavior of women at the Gaudi Makassar store with the coefficient of determination (adjust R square) shows that the independent variables in this study have an effect of 43.4% and the remaining 56.6% is influenced by other variables outside this study.